Testosterone up-regulates vacuolar ATPase expression and functional activities in vas deferens of orchidectomized rats - Ramli, Nur Siti Khadijah; Giribabu, Nelli; Muniandy, Sekaran; Salleh, Naguib (Elsevier, 2018)
Precise regulation of vas deferens fluid pH is essential for sperm. However, the mechanisms underlying effect of testosterone on vas deferens fluid pH have never been identified, which could involve changes in expression and functional activity of vacoular (V)-ATPase. Methods Orchidectomized, adult male Sprague-Dawley rats were treated subcutaneously with 125 μg/kg/day and 250 μg/kg/day testosterone with or without flutamide (androgen receptor blocker) and finasteride (5α-reductase inhibitor) for seven (7) days. Following treatment completion, in vivo perfusion of vas deferens lumen was performed and changes in fluid secretion rate, pH and HCO3 − content were measured with and without bafilomycin, a V-ATPase inhibitor. Rats were then sacrificed and vas deferens were harvested and subjected for V-ATPase A1 and B1/2 protein expression and distribution analysis by western blotting and immunohistochemistry, respectively. Results In sham-operated and testosterone-treated orchidectomized rats, higher fluid secretion rate, which was not antagonized by bafilomycin but lower HCO3 − content and pH which were antagonized by bafilomycin were observed when compared to orchidectomized-only and orchidectomized, testosterone-treated rats receiving flutamide or finasteride, respectively. Bafilomycin had no effect on fluid secretion rate, HCO3 − content and pH in orchidectomized and testosterone-treated orchidectomized rats receiving flutamide and finasteride. V-ATPase A1 and B1/2 proteins were expressed at high levels in vas deferens and were highly distributed at the apical membrane of luminal epithelium and in muscle layer of this organ, mainly in sham and testosterone-treated orchidectomized rats. Conclusions V-ATPase is involved in acidification of vas deferens fluid under testosterone influence.